Strategi Pengembangan Kemasan Berbasis Kualitas Untuk Produk Ikan: Studi Implementasi di Desa Tlesah, Pamekasan - Rina Susanti; Mohammad Rudiyanto (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2024)
This study aims to evaluate quality-based packaging development strategies for fish products in Tlesah Village, Tlanakan Sub-district, Pamekasan Regency. The applied packaging uses vacuum heating and thermal coating technology to improve the freshness and shelf life of fish products. The research methodology included a qualitative design with a comprehensive assessment of the existing packaging conditions, application of the new technology, and evaluation of the results through laboratory tests and market surveys. The results showed that the new packaging increased the shelf life of fish products by 30%, with a 40% reduction in trimethylamine (TMA) levels compared to the old packaging. Consumer surveys revealed a 90% increase in satisfaction, and sales data showed a 25% increase in product sales with the new packaging. Challenges included initial costs for packaging materials and technology, and the need for external support. The research suggests continuous improvements in packaging techniques and materials and provides practical recommendations for processor groups and stakeholders. Implications for future research include exploring factors of packaging adoption in different contexts and developing innovations in environmentally friendly packaging materials.